Defining Small-Scale Fisheries and Examining the Role of Science in Shaping Perceptions of Who and What Counts: A Systematic Review - Smith, Hillary; Basurto, Xavier (Frontiers in Marine Science, 2019)
Small-scale fisheries (SSF) have long been overshadowed by the concerns and perceived importance of the industrial sector in fisheries science and policy. Yet in recent decades, attention to SSF is on the rise, marked by a proliferation of scientific publications, the emergence of new global policy tools devoted to the small-scale sector, and concerted efforts to tally the size and impacts of SSF on a global scale. Given the rising tide of interest buoying SSF, it’s pertinent to consider how the underlying definition shapes efforts to enumerate and scale up knowledge on the sector—indicating what dimensions of SSF count and consequently what gets counted. Existing studies assess how national fisheries policies define SSF, but to date, no studies systematically and empirically examine how the definition of SSF has been articulated in science, including whether and how definitions have changed over time. We systematically analyzed how SSF were defined in the peer-reviewed scientific literature drawing on a database of 1,724 articles published between 1960 and 2015. We coded a 25% random sample of articles (n=434) from our database and found that nearly one-quarter did not define SSF. Among those that did proffer a definition, harvest technologies such as fishing boats and gear were the most common characteristics used. Comparing definitions over time, we identified two notable trends over the 65-year time period studied: a decreasing proportion of articles that defined SSF and an increasing reliance on technological dimensions like boats relative to sociocultural characteristics. Our results resonate with findings from similar research on the definition of SSF in national fisheries policies that also heavily rely on boat length. We call attention to several salient issues that are obscured by an overreliance on harvest technologies in definitions of SSF, including dynamics along the wider fisheries value chain and social relations such as gender. We discuss our findings considering new policies and emerging tools that could steer scientists and practitioners toward more encompassing, consistent, and relational means of defining SSF that circumvent some of the limitations of longstanding patterns in science and policy that impinge upon sustainable and just fisheries governance.